2022
DOI: 10.1155/2022/8356256
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Foot and Hand Massage on Abdominal Pain of Cesarean Section Incision under Ultrasound Guidance

Abstract: In order to relieve the pain of incision after cesarean section, a method of foot and hand massage for abdominal pain of cesarean section incision under ultrasound guidance was proposed in this paper. In this paper, the experimental control method and retrospective analysis were used to relax the patients through massage, so that the pregnant women could focus on the reaction caused by hand and foot massage, distract their attention, and reduce the pain. The results showed that 60 cases of puerpera after cesar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Pain intensity pre- and post-60–90 minutes after massage was reported in six studies with 518 patients included. ( 9 , 11 , 17 20 ) The pooled MD favored the massage group over the control (MD = −2.50, 95% CI [−2.73, −2.27], p > .00001). The pooled studies were homogenous (χ 2 p = .60, I 2 = 0%) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Pain intensity pre- and post-60–90 minutes after massage was reported in six studies with 518 patients included. ( 9 , 11 , 17 20 ) The pooled MD favored the massage group over the control (MD = −2.50, 95% CI [−2.73, −2.27], p > .00001). The pooled studies were homogenous (χ 2 p = .60, I 2 = 0%) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 98%
“…We rejected 31 of these; eventually, 10 articles met our criteria and were included in our meta-analysis, while five studies were only included as a systematic review. ( 8 , 9 , 10 , 11 , 16 – 21 , 22 – 26 ) Figure 1 shows the PRISMA flow diagram for the study selection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%